Hybridity, Intersection, and Challenge: Navigating the History of Customary and Islamic Family Law in Moluccan Marriages - Tabroni, Roni; Izudin, Ahmad; Isnanto, Muh.; Sujibto, ⁠B. J.; Yuwono, ⁠Dandung Budi; Suarsana, ⁠I Made (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
The relationship between local traditions and Islamic family law primarily revolves around marriage, kinship, inheritance, and female’s roles within the family. However, this focus tends to emphasize gender roles, family authority, and individual rights, overlooking the intricate negotiations of values between Islamic traditions and local norms. This raises important questions about how these negotiations occur, the points of convergence, and the challenges faced in establishing a unique local Islamic family identity and legal framework. This study, which examines cases in Negeri Morella, Central Moluccas, aims to address these questions. The findings indicate that the negotiation process has been ongoing for a significant period, heavily influenced by the maternal-oriented Austronesian culture, which has contributed to a distinct Islamic identity within the community. This development has been shaped by the Sufism movement, which emphasizes human excellence (ihsān) at the family level. The negotiations occur at the intersection of customary values and Islamic marriage norms, significantly influenced by the clan (soa), which plays a crucial role as both a customary and religious authority. Although there is apparent harmony, the Morella community faces significant challenges, including tensions between orthodoxy and heterodoxy of religiosity, socio-cultural conflicts, the marginalization of women’s roles during spiritual transitions, and the predominance of Islamic law practices over customary law. This research provides valuable insights into the discussion surrounding the hybridity debate of Islamic family law, particularly regarding the perspectives of puritanical Muslims who often decline indigenous practices of Islamic law. [Interaksi antara tradisi lokal dan hukum keluarga Islam umumnya terfokus pada pernikahan, kekerabatan, warisan, dan posisi perempuan dalam keluarga. Namun, persinggungan tersebut hanya menyoroti peran gender, otoritas keluarga, dan hak-hak individu, sehingga mengabaikan kompleksitas negosiasi norma antara keaadatan dan keislaman. Hal ini mengundang perdebatan lanjutan tentang bagaimana proses negosiasi, titik temu, dan tantangan yang berlangsung dalam pembentukan identitas Muslim Maluku. Melalui eksplorasi kasus di Negeri Morella, Maluku Tengah, studi ini berusaha mencari jawaban atas tiga perdebatan tersebut. Fakta menunjukkan bahwa proses negosiasi telah terjalin cukup lama yang sangat erat dipengaruhi oleh Austronesian culture yang lebih bersifat maternal, dengan membentuk sebuah identitas Islam yang khas bagi komunitas lokal. Ini terjadi karena pengaruh gerakan Sufism yang membentuk human excellence (ihsān) ke dalam unit kecil, seperti keluarga. Dasar negosiasi ini berlanjut pada titik temu antara nilai-nilai adat dengan norma pernikahan Islam. Perjumpaan ini sangat kuat dibentuk oleh pengaruh clan (soa), dengan peran pentingnya sebagai tokoh adat dan agama sekaligus. Meskipun tampak harmonis, komunitas Morella masih menghadapi tantangan serius, seperti ketegangan antara ortodoksi dan heterodoksi keagamaan, konflik sosial-budaya, marginalisasi peran perempuan dalam transisi spiritual, serta dominasi praktik hukum Islam atas hukum adat. Studi ini menawarkan kontribusi penting dalam perdebatan hibriditas hukum keluarga Islam, terutama terhadap sikap kelompok Muslim puritan yang cenderung menolak praktik-praktik indigenisasi hukum Islam.]